Why inhibitors of mammalian target of rapamycin will be important in organ transplantation - Brockmann, J; Friend, P (2004)
Drugs using inhibitors of mammalian target of rapamycin provide a real opportunity to treat patients with much lower exposure to calcineurin inhibitors. Long-term studies remain to be completed that show whether this might lead to important reductions in drug-related kidney damage. Evidence is starting to accumulate that the use of a mammalian target of rapamycin inhibitor early after transplantation might be contraindicated because of impairment in tubular regeneration. © 2004 Lippincott Williams and Wilkins.